Investigation of disorder in mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon - Patil, Sumati; Kolekar, Sadhu; Kumar, Arvind; Alegaonkar, Prashant; Datar, Suwarna; Dharmadhikari, C. V. (Journal of Nanoscience and Nanotechnology, 2018)
Disorder in a mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon (GNC) lattice has been extensively studied for its electronic and field emission properties. Morphological investigations are performed using scanning electron microscopy (SEM) which depicts microstructures comprising of atomically flat terraces (c-planes) with an abundance of edges (ab planes which are orthogonal to c-planes). Scanning tunneling microscopy (STM) is used to observe the atomic structure of basal planes whereas field emission microscopy (FEM) is found to be suitable for resolving nanotopography of edges. STM images revealed the hexagonal and non-hexagonal atomic arrangements in addition to a variety of defect structures. Scanning tunneling spectroscopy is carried out to study the effect of this short-range disorder on the local density of states. Current versus voltage (I-V) characteristics have been recorded at different defect sites and are compared with respect to the extent of the defect. As sharp edges of GNC are expected to be excellent field emitters, because of low work function and high electric field, enhancement in current is observed particularly when applied electric field is along basal planes. Therefore, it is worthwhile to investigate field emission from these samples. The FEM images show a cluster of bright spots at low voltages which later transformed into an array resembling ledges of ab-planes with increasing voltage. Reproducible I-V curves yield linear Fowler-Nordheim plots supporting field emission as the dominant mechanism of electron emission. Turn on field for 10 mu A current is estimated to be similar to 3 V/mu m.
Keywords: Field emission microscopy; Graphene-Like Nanocarbon; Scanning tunneling microscopy; Scanning Tunneling Spectroscopy

Interface-centric strategies in kesterite solar cells: addressing challenges, solutions, and future directions for efficient solar-harvesting technologies - Jagadish, Kusuma; Rahane, Ganesh K.; Kumar, Boddeda Sai; Borkar, Durgesh R.; Chordiya, Kalyani; Kavanagh, Sean R.; Roy, Anurag; Debnath, Tushar; Kolekar, Sadhu; Kahaly, Mousumi Upadhyay; Mali, Sawanta S.; Pal, Shovon; et al. (SMALL, 2024)
Keywords: band engineering; Defects; interface loss mechanism; kesterites; recombination control; solar energy